Uncertainty about COVID-19 disease among nurses in hospitals in Morelia, Mexico - Ruiz-Recéndiz, Ma. de Jesús (Universidad de Sonora, 2021)
Introduction: The outbreak of emerging diseases such as COVID-19 has caused a series of alterations in people, including nurses, who are in the first line of care. Some of the effects include the presence of anxiety, depression, stress, insomnia, and anguish. Objective: Evaluate the level of uncertainty about COVID-19 disease in second-level nursing staff in Morelia, Michoacán, Mexico. Methodology: Descriptive and cross-sectional study, in a sample of 160 nurses from public and private second-level care hospitals, non-probabilistic convenience sampling contacted via Facebook. Nurses in direct patient care were included, using the modified community version of the Illness Uncertainty Scale and a sociodemographic and occupational data questionnaire. Descriptive statistics and chi-square were used. The anonymity of the participants was respected. Results. Most of the participants were women (87.5%), licensed nurses (63.1%), mean age 36.7 years (SD=8.5) and 36.9% had been in contact with COVID-19 patients. Total uncertainty was moderate in 56.9% and in nursing personnel in contact with COVID-19 patients it was 64.8%. A statistically significant relationship (p=≤0.05) was found between uncertainty and sex, schooling; COVID-19 training and use of personal protective equipment; availability of face shield and personal protective equipment; have taken COVID-19 course and have had contact with COVID-19 patients. Conclusions. There was moderate uncertainty in the nursing personnel working at second-level care hospitals, with differences in personal variables, training and availability of material and equipment.